Factors of Sustainable Development in the Formation of the Value of Manufacturing Companies - Yu. Yu. Savchenko (Мир новой экономики)
The relevance of the research is justified by the need to search for new factors of business value formation, which are taken into account by stakeholders when making decisions.   The purpose of the article is to analyze the influence of S- and G- factors on the value formation of Russian public companies in the manufacturing sector and to substantiate the importance of disclosing the indicators of sustainable development of companies as a factor of business growth.   The study uses methods and tools of correlation, causal and comparative analysis. It was found that the position occupied in the RAEX ranking by S- and G- factors and the amount of capitalization are significantly correlated for companies in the extractive and manufacturing industries. There was found no statistically significant relationship between the considered indicators in relation to the companies of the agro-industrial complex. It is confirmed that the influence of sustainable development components on the formation of the companies’ value is different depending on their industry affiliation. The necessity to take into account ESG factors in the methods of comparative and income approaches is substantiated. The directions of ESG factors accounting in the methods of comparative and income approaches are highlighted.   The scientific novelty of the research is determined by the substantiation of the necessity of separate accounting of the sustainable development components in the formation and assessment of business value.   The practical significance of the study is that the results obtained by the author can be used by investors, owners and practicing appraisers in making managerial decisions and assessing and determining business value.